Types of Rhyme and Radif and Their Musical Roles in Iraqi's sonnets - Abdolreza Seyf; Ali Mohammad Moazzeni; ALIASGHAR FARAZ (مطالعات زبانی و بلاغی)

(untitled)
The verbal music in poem, named  aesthetics, is the first and most important element of the beauty of poem and can fascinates addressee. Rhyme, radif in verbal music plays a very important role and serves as a pillar and reference in the music of every line. In this text, we explore types of rhyme and radif and their musical roles in Iraqi's sonnets. Iraqi is the great mystic and poet who lived in 7th century. We evaluated rhyme and radif, used in his poem book from different angels, in a descriptive-analytical way. The following results were achieved: Sonnets, have used common and frequently used rhythms.  His expression is fluent and understandable. 63% of the rhyme words  are ended with high syllable, in form of obligated  mordaf  to main redf and absolute mordaf to main redf. This issue provides the context for music of word and beautifies the thoughts. 24% of the rhymes ended with simple syllable have been in obligated and absolute form. In these  rhymes, for having the necessary condition for fluency of the music, vowels or a suitable radif with a high syllable have been used. 64% of Iraqi's sonnets have radifs, so the last consonant of the rhyme with poor pronunciation in these sonnets is well-pronounced and the necessary music of the poem is achieved. The phonetic relationship between the chains and sub-chains in the chain of words, between rhyme and radif, and the other words in each line has a good harmony and nice beautiful music.But in Iraqi's sonnets, contents are similar and  imagination is low, and repetitions of rhyme,  radif and the first line (Matla') are in excess of need.